Kepuasan Kerja, Komitmen Organisasi Dan Semangat Kerja Karyawan Pada PDAM Tirta Sukapura Tasikmalaya - Dian Kurniawan; Irman Firmansyah (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
One of the important strategies in runninga businessis to maintain employee morale. However,the spirit must be supported with the factors that influence it. Therefore, this study aimed to measure whet her job satisfaction and organizational commitment affects employee morale. This study was conducted to employees of PDAM TirtaSukapura, Tasikmalaya by the number of respondents was 198 people. The results showed that job satisfaction significantly influence organizational commitment, organizational commitment have a significant effecton morale, job satisfaction have a significant effecton morale, and organization commitment mediates the relationship between job satisfaction on morale. It is thus that employee morale PDAM Tirta Sukapura influenced by job satisfaction and organizational commitment.